CITRA PEREMPUAN DALAM MEDIA - Robeet Thadi (Institut Agama Islam Negeri Bengkulu, 2014)
The appearance of women in the media can be seen from the meaning contained in the payload information intrinsically demeaning women, that makes women as the object of the ruling party, especially the economy. Discourse that degrades the position of women there that are open (overt) and manifest, so easily identified, such as the exploitation of the body in a sexual context and purpose of sensuality. While some are hidden (latent), such as the exploitation of women's bodies such as the quality of beauty, slenderness, whiter skin in the context of commercialism. The image formed by the media will affect the audience in perceiving one's view of others as well as the views of women.